Use of response guilds of understory birds in threatened subtropical forest to monitor selective logging impact. (December 2021) - Tallei, Ever; Rivera, Luis; Schaaf, Alejandro; Vivanco, Constanza; Politi, Natalia
Highlights: We use species of understory birds as response guilds to the impact of logging. Guild of logged sites was associated with greater visual obstruction of the understory. Guild of unlogged sites was associated with a higher density of dead and timber trees. Response guild monitoring can be used for sustainable forest management. Abstract: Unplanned logging is one of the greatest current threats to native forests biodiversity. About 90% of the piedmont forest in the Southern Andean Yungas has been converted to other land-use types and the remaining forests fragments are being intensively logged without management plans. Bird species, especially understory birds, are good indicators of forest diversity and integrity. The aim of this study was to identify understory bird species associated with changes in the forest structure caused by selective logging and to explore whether it is possible to use these species as a monitoring tool. We observed that Sittasomus griseicapillus, Turdus rufiventris, Lepidocolaptes angustirostris, Casiornis rufus, Thraupis sayaca, and Tolmomyias sulphurescens were associated to unlogged sites with higher density of timber-yielding and standing dead trees. Thamnophilus caerulescens, Leptotila megalura, Synallaxis scutata, Poecilotriccus plumbeiceps, and Catharus ustulatus were favoured by logging activities and associated with understory visual obstruction. Mean cut-off abundance thresholds were 2.74 ind/ha for the avian guild associated with unlogged forest and 1.79 ind/ha for the guild associated with logged forest. Sustainable forest management schemes need to retain the understory visual obstruction at values similar to those of unlogged forest (43.75%), together with an adequate density (≥10 ind/ha) of standing dead trees with at least 19.5 cm in DBH, and a minimum of 210 ind/ha of timber tree species. Bird species identified in this study can be used in monitoring schemes to evaluate the implementation of these guidelines.